Improving Students’ Argumentative Writing Skills through Constructivist-Based Project-Based Learning in Indonesian Language Education - Azmi Yuliana; Halimatun Syakdiah (Sean Institute, 2026)
This study investigated the effectiveness of constructivist-based Project-Based Learning in improving students’ argumentative writing skills in Indonesian language education. The study employed a quantitative approach with a quasi-experimental pretest-posttest design involving 32 students. The intervention was implemented through structured learning stages, including issue orientation, project planning, inquiry and evidence collection, argument construction, drafting and feedback, revision, and final presentation. Data were collected using an argumentative writing test assessed through five components: thesis or claim clarity, argument development, evidence and reasoning, counterargument and refutation, and organization and language use. The results showed that students’ mean score increased from 61.84 in the pretest to 82.19 in the posttest, with a mean difference of 20.35 points. The normality test indicated that the data were normally distributed, and the paired-sample t-test confirmed a significant improvement in students’ argumentative writing skills, t(31) = 17.84, p < 0.001. The normalized gain score was 0.53, which was categorized as moderate. These findings indicate that constructivist-based Project-Based Learning is effective in supporting students’ ability to formulate claims, develop arguments, use evidence, address counterarguments, and organize argumentative texts coherently.